Vibration reduction of a rotating machine using resonator rings. (July 2020) - Prado, L.S.; Ritto, T.G.
Highlights: The goal is to create a band gap around a critical speed of a rotating machine. Resonator rings are proposed to reduce rotordynamics lateral vibrations. The resonators are attached to the shaft and rotate with it. Campbell diagram and the frequency response are analyzed. Abstract: This paper proposes the application of resonator rings to reduce the amplitude of lateral vibrations of rotating machines. The resonator is composed of four beams attached to a rigid cylinder at the shaft position and a flexible ring at the other extremity. A continuous model, discretized by means of the finite element method, is considered with a shaft, one disk, two rigid bearings, and several resonator rings. The Campbell diagram and the response of the system in the frequency domain are analyzed. It turns out that the proposed resonator gives good results: the designed resonator is able to create a band gap around a target critical speed.